Post-Marketing Surveillance of a generic Oxaliplatin (AlvoxalⓇ) in Iranian Patients with Cancer - Farhad Shahi; Mojtaba Gorji, Assistant Professor of Pediatric Oncology; Mehrdad Payandeh, Assistant Professor of Hematology & Oncology; Hamid Rezvani, Associate Professor of Hematology & Oncology; Mohammad Vaezi, Associate Professor of Hematology & Oncology; Sharareh Seifi, Assistant Professor of Hematology & Oncology; Alireza Baari, Post doctoral fellowship; Reza Khalili-Dizaji, Post doctoral fellowship; Seyed Mehdi Hashemi, Associate Professor of Hematology & Oncology; Saeid Salimi, post doctoral fellowship; Hosein Kamranzadeh, Associate Professor of Hematology & Oncology; Babak Shazad, Post doctoral fellowship; et al. (Elsevier, 2022)
ABSTRACT: Background: CRC is the second and third most common cancer in women and men, respectively. The national comprehensive cancer network guidelines recommend oxaliplatin-based chemotherapy as a preferred regimen for patients with advanced or metastatic colon cancer. Oxaliplatin is also used in the off-label treatment of gastric cancer. FDA uses post-marketing study commitments to gather additional information about a product's safety, efficacy, or optimal use. It is necessary to perform safety monitoring after marketing authorization is received; such monitoring can be done by means of characterizing the safety of drugs in patients being treated in real-world clinical practice settings. Objectives: This Phase IV study aimed to evaluate the safety profile of a brand-name formulation of the generic drug oxaliplatin (AlvoxalⓇ, NanoAlvand, Tehran, Iran) in Iranian patients diagnosed with either colorectal or other, different types of cancer. Methods: Patients with colorectal cancer, gastric cancer, or other malignancies receiving oxaliplatin as a part of their treatment were included in this open-label, multicenter, observational Phase IV study. This study aimed to assess the safety profile of oxaliplatin in patients diagnosed with different cancers. Findings: A total of 483 patients from 16 cities in Iran were enrolled. The most common malignancy was colorectal cancer (55.49%), followed by gastric cancer (28.16%). Based on the results, 405 patients experienced at least 1 adverse event. Most of these adverse events were grade 1 or 2, and the most commonly reported adverse event was anemia (60.66%). During the study, 26 serious adverse events occurred in 15 (3.11%) patients, which were perhaps related to oxaliplatin. There were no remarkable differences in the incidences of adverse events in the system organ classes of blood and lymphatic system disorders, gastrointestinal disorders, or nervous system disorders among patients with different malignancies (ie, colorectal cancer, gastric cancer, and other malignancies) or between genders. The results of this open-label, multicenter, observational, postmarketing surveillance study demonstrated no unexpected safety findings from the use of this oxaliplatin product (AlvoxalⓇ) in Iranian patients diagnosed with different types of cancer. Conclusions: This Phase IV study provides data on the safety profile of a number of chemotherapy regimens containing an oxaliplatin product given to Iranian patients diagnosed with different types of cancer.